Acupuncture-related therapies for opioid-induced constipation in patients with cancer: a systematic review and network meta-analysis - Xinkun Liu; Huaqiang Shao; Jiayue Yang; He Chen; Ruimin Jiao; Guangxian Yu; Jiaxiang Shi; Wenquan Su; E. Zhang; Yiqi Liang; Zhishun Liu; Weiming Wang (Frontiers in Medicine, 2026)
Objectives To evaluate the efficacy and safety of acupuncture-related therapies for opioid-induced constipation (OIC) in patients with cancer through pairwise and network meta-analysis (NMA). Methods We searched eight electronic databases from inception to June 28, 2025, and identified randomized controlled trials (RCTs) evaluating acupuncture-related therapies for OIC in cancer patients, with or without laxatives. Pairwise and Bayesian NMA were performed using R. Primary outcomes included constipation-related symptoms and stool form, assessed using the Cleveland Constipation Scale (CCS), weekly spontaneous bowel movements (weekly SBMs), Bowel Function Index (BFI), Patient Assessment of Constipation Symptoms (PAC-SYM), and Bristol Stool Form Scale (BSFS). Treatments were ranked using the surface under the cumulative ranking curve (SUCRA), and the certainty of evidence was evaluated using GRADE. Results Thirty-six RCTs involving 3,351 participants and 15 acupuncture-related interventions were included. Direct evidence from pairwise meta-analyses and single-study comparisons suggested that some acupuncture-related therapies, alone or combined with osmotic laxatives (OSM), may improve CCS, weekly SBMs, BFI, PAC-SYM, and BSFS compared with OSM or other controls. In the NMA, AA+OSM, AP+OSM, and APA+OSM were associated with statistically significant reductions in BFI scores compared with OSM, although these estimates were supported by low-certainty evidence. No statistically significant differences were detected for CCS, weekly SBMs, PAC-SYM, BSFS, or PAC-QOL total score. Among studies reporting safety outcomes, adverse events were generally mild and infrequent, mainly gastrointestinal symptoms and local skin reactions. Most network estimates were based on sparse evidence and supported by low to very low certainty. SUCRA-based rankings were considered exploratory because several interventions were supported by only one trial and global inconsistency could not be formally assessed. Conclusion Acupuncture-related therapies may improve selected constipation-related symptoms and aspects of constipation-related quality of life in patients with cancer-related OIC. Reported adverse events were generally mild. However, these findings should be considered exploratory because the available evidence was limited and generally of low certainty. Systematic review registration The publicly accessible registration record is available at: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024598002 , PROSPERO CRD42024598002.